Analysis of Ecotourism Sustainability of Damaran Baru Protected Forest Area in Bener Meriah Regency - Wahyuni; Halus Satriawan; Rahmat Abbas (Jurusan Kehutanan Fakultas Pertanian Universitas Riau, 2024)
The existence of forests for village communities cannot be separated from the survival of communities around the forests. Utilization of environmental services in forest areas can take the form of ecotourism potential developed in the region. Ecotourism also embraces the use of environmental services in protected forest areas, including the Damaran Baru protected forest area. The current problem is that there is not yet optimal management of existing natural resource potential in order to support ecotourism development. The aim of this research is to analyze the potential supply and demand for ecotourism in the Damaran Baru protected forest area and to analyze the sustainability of ecotourism in the Damaran Baru protected forest. The research results obtained for supply potential data identified 12 ecotourism potentials in the form of coffee plantations in the area, waterfalls, primate monitoring posts, hot springs, bird monitoring posts, camping ground areas, pitcher plants, savanna, orchid beds, heli rocks, edelweis beds. and the peak of Damaran Baru. Likewise, for demand potential, it was obtained in terms of facilities and infrastructure that require improvement to attract more visitors. The results of the ecotourism sustainability research show that the level of visits to ecotourism locations has started to increase with a total of 200 visitors in 2022, where there was an increase in the number of visitors of 53.85% from the previous year.